Solar battery / Muhamad Fauzi Othman... [et al.] - Othman, Muhamad Fauzi; Abdul Rashid, Mohd Fazli; Awg. Noh, Mohd Lukman; Salleh, Mohd Zulkifli (Faculty of Mechanical Engineering, 2002)
It is a fact, that in future we should need an alternative way in generating power for human used to replace the unrenewable energy. It is due to the finding discovered out by the world researchers about the future of the unrenewable energy that can last about 50 to 100 years more. That is why we take an initiative to learn about this renewable energy for a future used in our country. It is totally advance for our country as it is located near the equator line, which deserved highest emission of solar regulation. From the facts, it is a waste if we do not use this advantage wisely to generate our country alternative energy supply. Therefore, in this thesis the mam point is that we want to study and learn about generating the electricity power using the solar energy and store the power in the battery. As we are taking the Diploma Mechanical in Automotive and to relate to our course in this thesis we only focusing upon the lead acid battery, which is often used in the automobile. Perhaps this study, we lead in creating a new creation to assist the changing process of the battery incase of sudden malfunction of the alternator, hopefully. Other than that, we are primarily concerned in the collection and storage of solar energy to make a comparison between solar charging and electric charging, and also to determine what the main effect and efficiency of solar charging. This book of thesis consists of the chapter overall. In the first chapter, we introduced about the thesis and our truth objectives of this thesis whereas in the second chapter, there was an explaining basically about the solar energy, the definitions of photovoltaic, a briefly about a panel technology and types of photovoltaic. While in the third chapter, we revealed about the battery operation and briefly about it working principle, voltage of the battery, constructions, ratings and efficiency. In the fourth chapter, we introduce about the battery storage, electrical components and the contents of the storage. For the chapter 5, we explain briefly about the equipments and installation. Meanwhile, in chapter 6, it was all about the result, analysis and briefly explanation about the graphs of the experiment. Lastly in chapter 7, we concluded the thesis and a little bit about the achievements and problem facing during the experiment.